Johann Joachim Winckelmann on art, architecture, and archaeology - Winckelmann, Johann Joachim, 1717-1768 (Studies in German literature, linguistics, and culture., 2013)
Modern English translations of several of the most important essays of Winckelmann, one of the fathers of art history and archaeology and a strong influence on Goethe and Schiller and Weimar Classicism.